Analysis of methods to assess the technological level and capabilities with suitable application for Vietnam condition - Hai, Nguyen Nam; Hoang, Nguyen Duc; Tung, Nguyen Khanh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2019)
Assessing the technological level and technological capability in manufacturing sectors are always very important for enterprises in the process of technology application and innovation as well as for state management agencies in managing science and technology activities in various industrial areas. Through the clarification of basic concepts related to technological level, technological capability and their assessment as well as analysis of science and technology evaluation methods, the authors have clarified the theoretical basis to assess technological level and technological capability in manufacturing sectors. Analyzing the experiences in evaluating technological level and technological capability of other countries in the world and that in Vietnam, the authors have clarified the practical basis from which to propose the method to evaluate technological level and technological capability applicable to the conditions of Vietnam. The proposed method and set of criteria for evaluating technological level and technological capability have been piloted and these results will create the basis for drafting the Circular guiding the assessment of technological level and technological capability in manufacturing sectors in Vietnam. Code: 19110401